2020
DOI: 10.1002/evl3.201
|View full text |Cite
|
Sign up to set email alerts
|

How does the strength of selection influence genetic correlations?

Abstract: Genetic correlations between traits can strongly impact evolutionary responses to selection, and may thus impose constraints on adaptation. Theoretical and empirical work has made it clear that without strong linkage and with random mating, genetic correlations at evolutionary equilibrium result from an interplay of correlated pleiotropic effects of mutations, and correlational selection favoring combinations of trait values. However, it is not entirely clear how change in the overall strength of stabilizing s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Nevertheless, covariance should principally build-up from linkage disequilibria within pairs, caused by correlational selection on the two traits. Note that the pleiotropic case is fully covered in Lande (1980 , 1984 ); Zhang and Hill (2003) ; Chantepie and Chevin (2020) .…”
Section: Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, covariance should principally build-up from linkage disequilibria within pairs, caused by correlational selection on the two traits. Note that the pleiotropic case is fully covered in Lande (1980 , 1984 ); Zhang and Hill (2003) ; Chantepie and Chevin (2020) .…”
Section: Modelmentioning
confidence: 99%
“…Correlational selection is when selection favors correlated values at phenotypic traits, which should translate into correlated genetic effects at the underlying loci affecting the traits. This has been shown to be the case in models attempting to approximate the level of genetic variance and covariance maintained at mutation-selection balance at pleiotropic loci affecting polygenic traits ( Lande 1980 ; Turelli 1985 ; Zhang and Hill 2003 ; Chantepie and Chevin 2020 ). For the case of tight linkage between pairs of loci affecting separate traits, Lande (1984) suggested that it “is nearly equivalent to” pleiotropic loci affecting both traits.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations